2022-RA-1443-ESGO Patient decision aids in genetic testing for women with ovarian cancer. (20th October 2022) - Sobocan, Monika; Chandrasekaran, Dhivya; Sideris, Michail; Blyuss, Oleg; Miller, Rowan; Mills-Baldock, Tina; Crusz, Shanthini; Sun, Li; Evans, Olivia; Jenkins, Lucy; Ahmed, Munaza; Kumar, Ajith; et al.
Abstract : Introduction/Background: Genetic-testing at ovarian cancer (OC) diagnosis is recommended in all clinical guidelines. The level of detailed information patients should be provided for informed decision making regarding genetic-testing is unknown. We evaluate patient preference for short or detailed/extensive Decision-Aids (DA) or written information-sheets for pre-test decision making. Methodology: A more detailed DA was developed using patient and stakeholder input following the principles/methodology of IPDAS (International Patients Decision Aids Standards). Unselected patients at OC-diagnosis were asked to evaluate both a pre-existing short and new long DA version. Patients then underwent mainstreaming genetic-testing by a cancer clinician. Data were collected on satisfaction, readibility, understanding, emotional well-being and preference for long/short-DA. Appropriate inferential descriptive and regression analyses were undertaken. Results: The mean-age of patients was 66-years (IQR=11), and 85% were white-British ethnicity. 74% found the DAs helpful/useful in decision making. Women reported higher levels of satisfaction (86% vs. 58%, p<0.001), right amount of information provided (76.79% vs.49.12%, p<0.001) and improved understanding (p<0.001) with the long-DA compared to short-DA. There was no statistically significant difference in the emotional outcomes (feeling worried/concerned/reassured/upset) between 'short' vs. 'long' DA. 74% patients preferred the long and 24% the short DA. Regression analysis suggested patients undergoing treatment (coeff=0.603; CI:0.165–1.041, p=0.007), those with recurrence (coeff=0.493; CI:0.065–0.92, p=0.024) and older women (coeff=0.042; CI:0.017–0.066, p=0.001) preferred the long-DA . Ethnicity did not affect any outcomes or overall preference for long/short-DA. 36% indicated they changed their decision regarding testing following mainstreaming counselling and 26% would have made the decision without it. Conclusion: A longer DA in OC patients has higher satisfaction without increasing any emotional distress. Older women and those undergoing treatment/recurrence prefer more extensive information, whilst those in remission preferred a shorter-DA.